Antisaccadic Training to Improve Impulsivity in Binge Eating Disorder. (25th July 2013) - Giel, Katrin Elisabeth; Schag, Kathrin; Plewnia, Christian; Zipfel, Stephan
Abstract: Patients with binge eating disorder (BED) show generally increased impulsivity and especially increased food‐related impulsivity. Both are closely linked to the core pathology of BED, which relates to regular binge eating episodes with experienced loss of control. The antisaccade task is an established paradigm assessing response inhibition as a pivotal component of impulsivity. It requires participants to execute antisaccades; that is, they are supposed to look in the opposite direction of a stimulus that automatically catches attention by appearing in the peripheral visual field. High rates of prosaccades to the peripheral stimuli are considered indicators of increased impulsivity. Presenting food pictures as peripheral stimuli, this task can be used to investigate food‐related impulsivity. We propose modifications of this task in order to design it as an antisaccadic training in which BED patients practise the suppression of food‐related responses, which should result in enhanced control over their eating behaviour. Copyright © 2013 John Wiley & Sons, Ltd and Eating Disorders Association.